Opening Address - LaRocque, Emma (Studies in Canadian Literature, 2006)
The overemphasis on supposed cultural differences between the “Indian” and the “White man” has contributed to the extreme marginalization of Native peoples. Nevertheless, and in spite of the ever-present millstone of colonization, Native writers continue to record historical and personal invasions, social upheavals, and personal losses with hope and determination. It has become clear that, if we are to escape the spectre of ghettoization, we must push, if not dismantle, the paradigms that restrict our identities to predetermined typologies. To acquiesce to colonial markers is to subordinate ourselves to the colonizer’s model of the world. To illustrate, LaRocque turns to the works of Jeannette Armstrong, Joy Harjo, Arthur Shilling, Thomas King, and Richard Wagamese.